2010
DOI: 10.1007/s11104-010-0569-x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of myrosinase from Sinapis alba seeds immobilized into Ca-polygalacturonate as a simplified model of soil-root interface mucigel

Abstract: Ca-polygalacturonate is a demethoxylated component of pectins which are constitutive of plant root mucigel. In order to define the role of root mucigel in myrosinase immobilization and activity at root level, a myrosinase enzyme which had been isolated from Sinapis alba seeds was immobilized into Capolygalacturonate. The activity profile for the immobilized and free enzyme was evaluated using the pH-Stat method as a function of time, temperature, and pH. The Michaelis-Menten kinetic parameters change between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In the absence of myrosinase no formation of 10 was observed (Figure A). Substrate conversion followed Michaelis–Menten kinetics with K m =888±143 μ m and a k cat of 37.9 s −1 (Figure ), that is, values within the range determined with natural GSLs …”
Section: Methodssupporting
confidence: 60%
“…In the absence of myrosinase no formation of 10 was observed (Figure A). Substrate conversion followed Michaelis–Menten kinetics with K m =888±143 μ m and a k cat of 37.9 s −1 (Figure ), that is, values within the range determined with natural GSLs …”
Section: Methodssupporting
confidence: 60%
“…At 65 C, the free enzyme activity was less than half of the When the temperature arrived at 75 C, the enzyme activity was decreased to 62% of the maximum enzyme activity. Another study reported a suitable temperature range of 50-60 C for immobilized MYR in Ca-polygalacturonate (Braschi et al, 2011). The improved heat resistance of the enzyme may due to that the MYR was adsorbed by SA and cross-linking with glutaraldehyde, after which enhanced the firmness of the enzyme configuration.…”
Section: Comparison On Characteristics Of Free and Encapsulated Myrmentioning
confidence: 99%
“…for MYR in immobilized Ca-polygalacturonate (Braschi et al, 2011). Increased suitable temperature and pH range for MYR would be beneficial for supplying encapsulated MYR as exogenous enzyme accompanied with GLs to promote SF production in vivo or vitro.…”
Section: Comparison On Characteristics Of Free and Encapsulated Myrmentioning
confidence: 99%
See 2 more Smart Citations